Establishing the constitution of Islamic state and its pillars in the light of Tafseer Tafheem ul Quran: إقامة دستور الدولة الإسلامية وركائزها في ضوء تفسير تفهيم القرآن لسيد أبو الأعلى المودودي رحمه الله - Khoso, Dr. Aijaz Ali; Hammad, Muhammad; Ahmed, Dr. Muneer (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Tafheem-ul-Quran is the combination of orthodox and modernist interpretation and has deeply influenced modern Islamic thought. It differs from traditional exegeses in several ways. It is more than a traditional commentary on the scripture as it contains discussions and debates regarding economics, sociology, history, and politics. In his text, Syed Abul A’la Maududi highlights Quranic perspective and argues that Islam provides ample guidance in all spheres. Syed Abul A’la Maududi uses the standard technique of providing an explanation of the Quranic verses from the Sunnah of Muhammed, including the historical reasons behind the verses. Tafhim-ul-Quran deals extensively with issues faced by the modern world in general and the Muslim community. And He did not believe in nationalism based on homeland, blood, language, or food, according to some customs of the Indian subcontinent, or the government, or other slogans that have no value to him. Rather, the concept of nationalism for him is based on religion. It is only Islam. Imam Mawdudi continued to spread the Islamic Dawah through his monthly magazine “Tarjuman al-Qur’an” his books, and lectures for more than eight years. He felt that quite a few new scholars and intellectuals were influenced by his Dawah, so he directed his Dawah to them to establish the Islamic group. And Imam Mawdudi called for the establishment of an Islamic state that derives its constitution from the Noble Qur’an and was subjected to a lot of harm to continue demanding the Islamic constitution and the application of Islamic Sharia. And there is no corner of it except that it is completely linked to Islam, for Islam is a complete system of life, and politics is one of the parts of this life.